'People can be smarter with two languages': changing anglophone students' attitudes to language learning through teaching linguistics*. Issue 1 (1st January 2019) - Lanvers, Ursula; Hultgren, Kristina; Gayton, Angela Mary
ABSTRACT: With English as an undisputed global lingua franca, there is long-standing concern in anglophone countries over the lack of interest in language learning. In the UK, significant changes in language education policy, a mentality of insularity and the global spread of English have all contributed to a drop in language learning uptake beyond the compulsory stage. While the UK has seen many initiatives aiming to foster language learning, no interventions so far have aimed to change learner attitudes by raising students' language awareness of (a) the spread of English globally, and (b) cognitive benefits of mulitilingualism, and the ubiquity of multilingualism, globally and in the UK. A teaching intervention designed for this purpose was delivered to 97 students aged 12–13 in three different state schools in England and Scotland. The effect of the intervention was measured by a pre- and post-questionnaire, with questions closely tailored to the content of the intervention. In addition, qualitative student feedback was gathered after the intervention. Results show significant changes, across the cohort, in two out of three constructs studied, and effects on students' attitude towards language learning. Thus, we conclude that raising anglophone students' awareness of language through raising awareness of cognitive benefits of multilingualism, and the spread of English globally, has the potential to change the attitudes of learners otherwise not interested in language learning.